2021
DOI: 10.3390/jcm10030374
|View full text |Cite
|
Sign up to set email alerts
|

The Shift from Multiport to Single Port Increases the Amount of Bleeding in Laparoscopic Major Hepatectomy

Abstract: Background: Bleeding is a negative outcome predictor in liver surgery. Reduction in the abdominal wall trauma in major hepatectomy is challenging but might offer possible benefits for the patient. This study was conducted to assess hemostasis techniques in single-port major hepatectomies (SP-MajH) as compared to multiport major hepatectomies (MP-MajH). Methods: The non-randomized study comprised 34 SP-MajH in selected patients; 14 MP-MajH served as the control group. Intraoperative blood loss and number of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Nearly all the case reports involved minor liver resections [partial hepatectomies, monosegmentectomies, and left lateral sectionectomies (LLS)]. Three of the eight original articles described major hepatectomies (resection of over two segments), including nine right hemihepatectomies (RHs), 34 left hemihepatectomies, and seven right posterior sectionectomies (RPSs)[ 27 , 29 , 32 ] (Table 1 ). Most procedures were performed for malignant diseases.…”
Section: Single-incision Laparoscopic Hepatectomy (Silh) For Malignancymentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all the case reports involved minor liver resections [partial hepatectomies, monosegmentectomies, and left lateral sectionectomies (LLS)]. Three of the eight original articles described major hepatectomies (resection of over two segments), including nine right hemihepatectomies (RHs), 34 left hemihepatectomies, and seven right posterior sectionectomies (RPSs)[ 27 , 29 , 32 ] (Table 1 ). Most procedures were performed for malignant diseases.…”
Section: Single-incision Laparoscopic Hepatectomy (Silh) For Malignancymentioning
confidence: 99%
“…Hyun et al [ 26 ] reported a shorter postoperative hospital stay and comparable pathologic features for minor SILH compared with minor MILH; long-term survival outcomes were absent. Mittermair et al [ 27 ] showed less blood loss, a lower number of patients with blood loss > 25 mL, and more blood transfusions in the major SILH group; no local tumor recurrence occurred during a median follow-up of 61 mo. Tsai et al [ 28 ] reported a shorter operative time and shorter postoperative hospital stays in the SILH group for LLS but not partial hepatectomies of segment 5-6; the 1-, 3-, and 5-year overall and recurrence-free survival rates for hepatocellular carcinoma were similar in both the SILH and MILH groups.…”
Section: Single-incision Laparoscopic Hepatectomy (Silh) For Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…These results were confirmed by a series from our department. Nevertheless, we observed an increased risk of substantial blood loss when bleeding occurs in these complex resections[ 40 ].…”
Section: Medusa the Power And Performancementioning
confidence: 99%